Global research status and trends of bronchiectasis in children from 2003 to 2022: A 20-year bibliometric analysis - Gong, Ting; Wang, Xueer; Li, Shuanglian; Zhong, Li; Zhu, Lin; Luo, Tingting; Tian, Daiyin (Frontiers in Pediatrics, 2023)
Background: This study aims to analyze the research hotspots, evolution and developing trends in pediatric bronchiectasis over the past 20 years using bibliometric analysis and visualization tools to identify potential new research directions. Methods: Publications related to bronchiectasis in children were retrieved from the Web of Science Core Collection (WoSCC) database for the period of 2003-2022. Knowledge maps were performed through VOSviewer1.6.18 and Citespace6.1 R2. Results: A total of 2133 publications were searched while only 1351 original articles written in English between 2003 and 2022 were incorporated. After removing duplicates, we finally included 1350 articles published by 6593 authors from 1865 institutions in 80 countries/regions on 384 different academic journals with an average citation frequency of 24.91 times. In total, the number of publications shows an extremely obvious binomial growth trend. The majority of publications originated from the United States, Australia and England. The institutes in Australia, especially the Charles Darwin University, published the most articles associated with pediatric bronchiectasis. In addition, Pediatric Pulmonology was the most published journal. In terms of authors, Chang AB was the most productive author while Gangell CL had the highest average citation frequency. The five keywords that have appeared most frequently during the last 2 decades were “children”, “cystic fibrosis”, “bronchiectasis”, “ct” and “pulmonary-function”. According to keyword analysis, early diagnosis and intervention, and optimal long-term pediatric-specific management were the most concerned topics for researchers. Conclusion: This bibliometric analysis indicates that bronchiectasis in children has drawn increasing attention during the last 2 decades as its recognition continues to rise, providing scholars in the field with significant information on current topical issues and research frontiers.